Application of a novel transcanal keyhole technique in endoscopic cholesteatoma surgery. (1st April 2021) - Hou, Zhaohui; Wang, Fangyuan; Zuo, Wenjing; Liu, Ya; Wang, Wenjia; Hou, Kun; Jia, Jianping; Yang, Shiming
Abstract: Background: It is difficult to deal with epitympanic cholesteatoma in otologic surgery. The keyhole technique can realize minimally invasive surgery and reconstruct the middle ear canal. Objective: To explore the clinical application of keyhole technique in primary and second-look surgery in middle ear cholesteatoma. Materials and Methods: 34 cases were analyzed retrospectively in terms of residual and recurrence rate, safety (adverse events) and hearing performance at long-term follow-up. The application of the technique in primary or second stage operation was evaluated and the operation was performed by transanal endoscopy or combined approach. Results: The cholesteatoma revealed by CT before operation was limited to the attic in 23 patients, of which 16 had the same imaging range as that of the keyhole technique. The preoperative imaging findings of 11 showed that the attic cholesteatoma may have extended into the mastoid, of which only 6 cases were confirmed by keyhole technique. An endoscopic second-look surgery using the keyhole technique was performed for these patients, 2 were confirmed to have residual lesions in the attic. Conclusions: The keyhole technique under otoendoscopy can be used flexibly and conveniently in the second-look surgery to make up for the shortage of diffusion-weighted magnetic resonance imaging.